THE INFLUENCE OF CLUE GAME TOWARDS STUDENTSâ€Ÿ GRAMMAR MASTERY AT THE SECOND SEMESTER OF THE EIGHTH CLASS OF MTs NEGERI KALIANDA LAMPUG SELATAN IN 2013/2014 - Wahyuningsih, Sri (Lentera: Jurnal Ilmiah Kependidikan, 2016)
The objective of the research is to know whether there is the influence of clue game towards studentsâ€Ÿ grammar mastery. The population sample of this research was 78 students; it consisted of 40 students in experimental class and 38 students in control class. The sampling technique is cluster random sampling technique. In collecting the data, the writer used objective test. The test consists of 40 items with four options. The subjective of teaching grammar mastery as enable students to communicate in English in real life situation and understand the meaning of English words. Based on the data analysis of data and hypothesis, the writer found that the average score of experimental class higher than the control class. Therefore, the writer would like to say that cooperative learning that can be used to improve studentsâ€Ÿ grammar mastery. It can be concluded that t test > t table. Ttest is = 4.002 and t table is = 1.995 (???? = 0.05) and 2.65 (???? = 0.01). It means that there is positive influence of teaching grammar mastery through cooperative learning towards studentsâ€Ÿ grammar mastery. There is significant Influence of â€œClue Gameâ€ towards studentsâ€Ÿ grammar mastery at the second semester of the eighth class of MTs Negeri Kalianda, Lampung Selatan. The average score of studentsâ€Ÿ grammar mastery who are taught by using â€œClue Gameâ€ is higher that studentsâ€Ÿ grammar mastery who were not taught by using â€œClue Gameâ€. It is proved by the average score of studentsâ€Ÿ grammar mastery in experimental class was higher than control class (61.64 > 50.32). Based on the calculation above, the writer concluded that there is a positive Influence of â€œClue Gameâ€ towards studentsâ€Ÿ grammar mastery at the second semester of the eighth class of MTs Negeri Kalianda, Lampung Selatan in 2013/2014.